АЛУНИТЫ ИЧЕТУЙСКОГО ПРОЯВЛЕНИЯ (ЗАПАДНОЕ ЗАБАЙКАЛЬЕ) - Избродин И.А.; Рипп Г.С.; Карманов Н.С. (My University, 2005)
Several generations of alunites with different chemical compositions were detected in Ichetuyskoye occur-rence of high aluminum rocks. Alunites are associated with pyrophyllite, muscovite, florencite, woodhouseite, svanbergite, barite, hydromica and some other minerals. There are often present Na-alunites with the higher Sr and Ca contents accompanied, simultaneously, by appearance of phosphate-ion. Composition of alunites, the ca-ses of gradual transitions between alunite and florencite, between natroalunite and its varieties enriched in Sr and Ca make evidence for widespread isomorphism of elements among cations and anions. As a result, the boundari-es between many mineral species and between groups of alunite, plumbogumite, bedantite become vague.
Keywords: 549.75(571.54)